Sintered copper paste for power device packaging and preparation method and application thereof
By using binder to coat components such as copper particles and rare earth antioxidants in copper paste, problems such as insufficient thermal conductivity of tin-based solder and oxidation of sintered copper materials are solved, and the reliability and mechanical strength of the packaging structure at high temperature are improved.
Patent Information
- Application Number
- CN202411873010.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-12-18
AI Technical Summary
The existing tin-based solder is insufficient in thermal conductivity under high temperature conditions, resulting in the problem of fatigue failure and thermal conductivity reduction in packaging during long-term high-temperature service. In large-area applications, sintered copper materials face problems such as surface oxidation, difficulty in controlling thickness uniformity and warping.
The copper particles coated with binder are combined with the synergistic effect of rare earth antioxidants and a variety of organic components. By forming a stable rare earth oxide barrier layer and chemical adsorption physical coating, the oxidation of copper particles is inhibited, and the moldability and thickness uniformity of the copper paste is ensured through molding agents and leveling agents.
It significantly enhances the adhesion and interface stability of the copper paste, improves the high-temperature service performance and oxidation resistance of the packaging structure, and ensures the reliability and mechanical strength of the connecting layer under high temperature conditions.
Smart Images

Figure CN119811742A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of third-generation semiconductor power device packaging, and in particular to a sintered copper paste for power device packaging, and a preparation method and application thereof. Background Art
[0002] With the rapid development of aerospace, electric vehicles and other fields, the performance requirements for core power devices are constantly increasing. Especially in high-power applications, third-generation wide-bandgap semiconductor materials (such as silicon carbide and gallium nitride) have gained widespread attention due to their high thermal conductivity and high temperature resistance. These materials can operate normally at temperatures of 350°C or even higher, meeting the reliability requirements under extreme conditions. However, if the interconnect material of the device package cannot match the high-temperature performance of the semiconductor material, it will become a bottleneck for system reliability.
[0003] The thermal conductivity and reliability of the packaging material directly determine the heat dissipation capacity and overall performance of the power module. At present, the packaging of devices such as silicon carbide usually uses tin-based solder to connect with the active metal ceramic substrate and the heat sink. However, the high-temperature performance of tin-based solder is poor. Its low melting point and thermal conductivity are not enough to meet the needs of high-temperature semiconductors. Especially when it is in service at high temperatures for a long time, the packaging may suffer from fatigue failure and reduced thermal conductivity. Therefore, sintered copper materials with good thermal conductivity and high temperature resistance are considered to be potential substitutes for tin-based solder.
[0004] However, large-area sintered copper materials still face many bottlenecks in practical applications. On the one hand, during the sintering process, the high activity of copper easily leads to surface oxidation, which in turn weakens the interfacial adhesion and long-term stability of the solder layer; on the other hand, the thickness uniformity of copper paste is difficult to control during large-area printing, which may lead to local weak areas. In addition, the copper layer often warps during the cooling process, which not only affects the flatness of the package, but also further deteriorates the thermal conductivity and mechanical properties of the solder layer. These problems severely limit the practical application of sintered copper materials in large-area high-temperature interconnections. Therefore, effectively inhibiting oxidation diffusion while ensuring thickness uniformity has become a key technical breakthrough for improving the performance of packaging structures.
[0005] In view of this, the present invention is proposed. Summary of the invention
[0006] The object of the present invention is to provide a sintered copper paste for power device packaging and a preparation method and application thereof, wherein the copper paste can solve the problems raised in the above-mentioned background technology.
[0007] The first aspect of the present invention provides a sintered copper paste for power device packaging, comprising the following raw materials in percentage by mass: 75%-85% of copper particles coated with a binder, and 15%-25% of an organic solvent system; the organic solvent system comprises a rare earth antioxidant; and further comprises: one or more of a forming agent, a leveling agent, a thickener, a cross-linking agent, a surfactant, a solvent, and a resin.
[0008] In the present invention, the rare earth antioxidant effectively inhibits the oxidation of the surface of the nano copper particles by forming a stable rare earth oxide barrier layer during the high temperature sintering process, and captures free oxygen through redox behavior, further slowing down the oxidation reaction. The molding agent is used to ensure the molding of the copper paste after printing, so as to achieve large-area printing and molding with uniform thickness. The leveling agent ensures that the thickness is uniform during double-sided brush paste printing. The uniform thickness of the slurry during the printing process is effectively guaranteed by the leveling agent. The thickness difference at different positions of the connecting layer after pre-sintering is less than 20μm, avoiding the performance loss caused by uneven thickness. The thickener is used to control the viscosity of the copper paste to ensure that it can maintain a suitable thickness and shape during the printing process. The cross-linking agent is used to enhance the adhesion between the sintered copper layers. The antioxidant and the high temperature stable cross-linking agent are combined to effectively control the oxidation problem during the sintering process and ensure the reliability of the connecting layer in long-term high temperature service. It is particularly suitable for the design of double-sided copper paste interconnection. The surfactant improves the dispersibility of copper particles in the solution, reduces the agglomeration of particles, and ensures the uniformity of the copper paste; the surfactant can also help improve the stability of the copper paste and reduce particle precipitation. Solvents are used to adjust the viscosity of copper paste, improve fluidity, ensure uniform dispersion of copper particles during printing, and avoid particle precipitation. Resins provide adhesion between copper particles, enhancing the adhesion and mechanical strength of the copper layer after sintering. The organic solvent system ensures that the copper paste has good formability, oxidation resistance, and thickness uniformity under high temperature conditions, and improves the dispersion of copper particles and reduces particle agglomeration.
[0009] Preferably, the binder comprises: one or more of polyvinyl pyrrolidone (PVP), methyl cellulose, ethyl cellulose, epoxy acrylate, acrylate and cellulose acetate.
[0010] Preferably, the organic solvent system comprises, by mass percentage, 1%-5% of a forming agent, 0.5%-2% of a leveling agent, 0.5%-1% of a thickener, 1%-3% of a rare earth antioxidant, 1%-3% of a crosslinking agent, 1%-2% of a surfactant, 85%-90% of a solvent and 1%-2% of a resin.
[0011] Preferably, the rare earth antioxidant includes one or more of cerium oxide (CeO2), lanthanum oxide (La2O3), cerium chloride (CeCl3) and lanthanum nitrate (La(NO3)3). Cerium oxide captures free oxygen to delay the diffusion of oxides, thereby improving the oxidation resistance, mechanical properties and high-temperature adhesion of the solder layer; lanthanum oxide is used to inhibit the oxidation reaction of copper particles by forming a stable oxide barrier layer during high-temperature sintering.
[0012] Preferably, the morphology of the copper particles includes one or more of spherical, flake or triangular.
[0013] Preferably, the particle size range of the copper particles is 50-2000 nm; more preferably, the particle size range of the copper particles is 100-1500 nm; further, the particle size of the copper particles is 100 nm, 300 nm, 500 nm, 800 nm, 1000 nm, 1200 nm, 1500 nm.
[0014] Preferably, the molding agent includes: one or more of polyvinylidene fluoride, polyacrylate, and styrene-butadiene copolymer.
[0015] Preferably, the leveling agent includes: one or more of sodium polyacrylate, ethoxy-modified silicone oil, and polyethylene glycol.
[0016] Preferably, the thickener includes: one or more of carboxymethyl cellulose (CMC), hydroxypropyl methyl cellulose (HPMC), and sodium polyacrylate.
[0017] Preferably, the cross-linking agent includes one or more of butyl methacrylate, butyl acrylate, and polyethyleneimine.
[0018] Preferably, the surfactant includes one or more of polyvinyl alcohol (PVA), polyoxyethylene octylphenol ether, and sodium dodecylbenzene sulfonate.
[0019] Preferably, the solvent is an alcohol organic substance; more preferably, the solvent includes: one or more of isopropyl alcohol, diisopropyl alcohol, triethylene glycol, terpineol, and α-terpineol.
[0020] Preferably, the resin includes: one or more of polyimide resin, amino resin, polyurethane resin; more preferably, the resin includes: one or more of bisphenol A type polyimide resin, bisphenol F type polyurethane resin or amino resin.
[0021] A second aspect of the present invention provides a method for preparing a sintered copper paste for power device packaging, comprising the following steps:
[0022] S1. Performing complex treatment on the copper particles to ensure that there is no oxide layer on the surface of the copper particles;
[0023] S2, mixing the copper particles treated with the complex with a binder, removing the supernatant by ultrasonic centrifugation, adding anhydrous ethanol for washing, and removing the supernatant by centrifugation to obtain copper particles coated with a binder;
[0024] S3, mixing a forming agent, a leveling agent, a thickener, a rare earth antioxidant, a crosslinking agent, a surfactant, a solvent and a resin, and stirring them uniformly to obtain an organic solvent system;
[0025] S4, mixing the copper particles coated with the binder obtained in step S2 with the organic solvent system obtained in step S3 to obtain the copper paste.
[0026] Preferably, step S1 comprises the following steps:
[0027] S11, dissolving a complexing agent in deionized water to obtain a complexing agent solution;
[0028] S12, adding copper particles to the complexing agent solution obtained in step S11, so that the oxide on the surface of the copper particles reacts with the complexing agent to form a soluble complex;
[0029] S13, centrifuging the mixture obtained in step S12 to remove the supernatant, and then washing with anhydrous ethanol and centrifuging to remove the supernatant;
[0030] S14, drying the cleaned copper particles to obtain copper particles with no oxide on the surface.
[0031] Preferably, the complexing agent includes: one or more of ethylenediaminetetraacetic acid (EDTA), nitrilotriacetic acid (NTA), citric acid, malic acid, oxalic acid or aminopolycarboxylic acid compounds; more preferably ethylenediaminetetraacetic acid and / or citric acid.
[0032] Preferably, the concentration of the complexing agent is 0.5%-2%, more preferably 0.8%-1.5%.
[0033] In some specific embodiments, step S1 includes the following steps:
[0034] S11, dissolving the complexing agent in deionized water, and stirring with a magnetic force until it is completely dissolved to obtain a complexing agent solution;
[0035] S12, adding copper particles to the complexing agent solution obtained in step S11, mixing at a solid-liquid mass ratio of 1:10-1:20, and magnetically stirring for 10-30 minutes to allow the oxide on the surface of the copper particles to react with the complexing agent to form a soluble complex;
[0036] S13, placing the mixture obtained in step S12 in a centrifuge, controlling the centrifugal speed at 5000-8000 r / min, the centrifugal time for 5-15 minutes, removing the supernatant, and then washing with anhydrous ethanol 2-3 times, centrifuging at 2000-4000 r / min for 5-10 minutes after each washing, and removing the supernatant to remove the complex and other residues;
[0037] S14, placing the cleaned copper particles in a vacuum drying oven at 60° C.-80° C. and drying for 30-60 minutes to obtain pure copper particles with no oxide residue on the surface.
[0038] Preferably, step S2 comprises the following steps:
[0039] The copper particles treated with the complex are mixed with an ethanol solution of a binder, ultrasonicated for 20-30 minutes, centrifuged at 4000-6000 r / min to remove the supernatant, then anhydrous ethanol is added for washing for 5-10 minutes, centrifuged at 2000-4000 r / min, and the supernatant is removed to obtain copper particles coated with a binder.
[0040] Preferably, step S3 comprises the following steps:
[0041] S31, dissolving the rare earth material in deionized water or an alcohol solvent, and magnetically stirring for 20-40 minutes to form a uniformly dispersed rare earth antioxidant;
[0042] Preferably, the concentration of the rare earth antioxidant is in the range of 0.1%-2%, more preferably 0.5%-1%;
[0043] S32. Add the components into the solvent in the proportion of rare earth antioxidant 1%-3%, molding agent 1%-5%, leveling agent 0.5%-2%, thickener 0.5%-1%, cross-linking agent 1%-3%, surfactant 1%-2%, solvent 85%-90%, and resin 1%-2%, and stir with a magnetic stirrer to ensure that the solution is evenly dispersed to obtain an organic solvent system.
[0044] Preferably, step S4 comprises the following steps:
[0045] S41, adding the binder-coated copper particles into an organic solvent system, and stirring with a magnetic stirrer for 20-30 minutes, so that the rare earth antioxidant and other organic components in the organic solvent system are evenly distributed on the surface of the copper particles, and a preliminary antioxidant treatment is achieved through chemical adsorption and physical coating;
[0046] S42, placing the mixture of step S41 in an ultrasonic bath, and ultrasonically dispersing the mixture at a temperature of 20-30° C. for 10-15 minutes to further enhance the adhesion and dispersion effect of the rare earth antioxidant and the organic component on the surface of the copper particles;
[0047] S43, placing the mixture after treatment in step S42 in a centrifuge, controlling the centrifugal speed at 5000-8000 r / min, the centrifugal time at 5-15 minutes, removing the supernatant, and retaining the copper paste attached with the rare earth antioxidant and the organic component.
[0048] A third aspect of the present invention provides an application of a sintered copper paste for power device packaging, which is applied in the packaging interconnection structure of the power device.
[0049] Preferably, it is used in the sintering connection process between the substrate and the heat sink.
[0050] In a fourth aspect of the present invention, a packaging interconnection structure of a power device is provided, comprising: a substrate, a heat sink, and a connection layer for connecting the substrate and the heat sink, wherein the connection layer is formed by the copper paste coated on both sides under pressure-assisted sintering to ensure complete interconnection of the double-sided copper paste. With this structure, oxides can be prevented from diffusing to the interface under high temperature conditions, thereby enhancing the reliability of the overall structure.
[0051] Preferably, the substrate is a DBC substrate, more preferably an active metal substrate with a metallized surface, specifically including: a bare copper active metal welded ceramic substrate, a silver-plated active metal welded ceramic substrate, and a nickel-gold-plated active metal welded ceramic substrate.
[0052] Preferably, the heat sink may be a copper plate, an aluminum plate, a nickel-plated copper plate or a nickel-plated steel plate to meet the thermal conductivity and high temperature resistance requirements of different packaging needs.
[0053] A fifth aspect of the present invention provides a method for preparing a packaging interconnection structure of a power device, comprising the following steps:
[0054] P1. Remove pollutants from the surface of the substrate and heat sink;
[0055] P2. Coating the copper paste on the connection surfaces of the substrate and the heat sink respectively, and pre-drying the coated substrate and the heat sink;
[0056] P3. Align and stack the pre-dried substrate and heat sink, place the stacked assembly in a sintering device, heat the sintering device and apply pressure to complete the sintering connection process, so that a dense and high-strength connection layer is formed between the substrate and the heat sink;
[0057] P4. Gradually lower the temperature of the sintering equipment and cool the stacked assembly to room temperature to obtain the packaging interconnection structure of the power device.
[0058] In some specific embodiments, a method for preparing a package interconnect structure of a power device comprises the following steps:
[0059] P1. Use a dust-free cloth to clean the surface of the DBC substrate and heat sink to be interconnected to remove all contaminants to ensure the adhesion of the copper paste;
[0060] P2. Coat the copper paste on the connection surfaces of the DBC substrate and the heat sink respectively, and control the coating thickness within the range of 50-200 μm to ensure the uniformity of the double-sided interconnection structure; place the coated DBC substrate and heat sink in a drying oven for pre-drying, and introduce nitrogen / argon / hydrogen / formic acid atmosphere to avoid oxidation. Control the drying temperature at 100-120°C and keep it for 30-60 minutes to achieve preliminary curing;
[0061] P3. Align and tightly stack the pre-dried DBC substrate and heat sink, place the stacked assembly in a sintering device, heat to 200-250°C, and apply a pressure of 5-20MPa for 2-8 minutes to complete the sintering connection process to ensure complete curing and tight bonding of the double-sided copper paste connection layer;
[0062] P4. Gradually lower the temperature of the equipment and slowly cool the sintered stacked assembly to room temperature to ensure that the connection layer does not crack or warp during the cooling process, thereby obtaining the packaging interconnection structure of the power device.
[0063] The present invention has at least the following beneficial effects:
[0064] (1) The present invention can significantly enhance the adhesion and interface stability of the copper paste by coating the copper particles with a binder, and the binder has excellent stability in a high temperature environment, which can ensure that the connection layer coated with double-sided copper paste maintains excellent adhesion and long-term reliability under extreme high temperature conditions, thereby effectively improving the high temperature service performance of the package interconnection structure.
[0065] (2) The present invention uses the synergistic effect of rare earth antioxidants and other organic components to enable copper particles to have excellent antioxidant ability, while ensuring that the copper paste has good dispersibility, formability and thickness uniformity during the sintering process, meeting the reliability requirements of high-temperature packaging.
[0066] (3) The multiple organic components and adhesive system for enhancing adhesion used in the present invention enable the copper paste to remain stable under extreme conditions, the connecting layer is not easy to crack, it has high high temperature service capability, and has excellent mechanical strength, and is suitable for high temperature packaging applications of DBC substrates and heat sinks.
[0067] (5) In the preparation method of the present invention, the copper particles are treated with a complex, thereby greatly improving the shear strength of the connecting layer after the copper paste is sintered.
[0068] (6) The present invention adopts double-sided copper paste coating and pressure-assisted sintering process to achieve reliable interconnection and high-strength adhesion of copper paste at high temperature. In addition, the double-sided coated copper paste design can effectively inhibit the diffusion of oxides at the interface under high temperature conditions, thereby significantly improving the anti-oxidation performance of the packaging structure. BRIEF DESCRIPTION OF THE DRAWINGS
[0069] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0070] Figure 1 The present invention is a schematic flow chart of a method for preparing a sintered copper paste for power device packaging.
[0071] Figure 2 This is a schematic diagram of the packaging interconnect structure of the power device provided by the present invention before and after sintering.
[0072] Figure 3 This is a diagram for selecting test points for the uniformity of copper paste coating thickness provided by the present invention.
[0073] Figure 4 This is a graph showing the shear strength test results of the connecting layer provided by the present invention at different temperatures and pressures.
[0074] Figure 5 This is an ultrascan image of the sintered connection layer provided by the present invention; wherein (a) is the connection layer of Example 1, and (b) is the connection layer of Example 2.
[0075] Figure 6 The diagrams are comparative test diagrams of the anti-oxidation performance of the connecting layer provided by the present invention under high temperature environment; wherein, (ab) are cross-sectional SEM images of the single-sided printed copper paste after high temperature aging after sintering; (c) is an EDS image of the single-sided printed copper paste after high temperature aging after sintering; (de) is a cross-sectional SEM image of the double-sided printed copper paste after sintering and high temperature aging; (f) is an EDS image of the double-sided printed copper paste after sintering and high temperature aging.
[0076] Figure 7 The present invention provides a comparison chart of the shear strength of the connecting layer after high-temperature aging at 250° C. at different times with and without rare earth oxidant treatment.
[0077] Figure 8 This is a graph showing the shear strength test results of the connecting layer treated with and without the complex provided by the present invention. DETAILED DESCRIPTION
[0078] It should be noted that the following detailed descriptions are illustrative and are intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present application belongs.
[0079] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit the exemplary embodiments according to the present application. As used herein, unless the context clearly indicates otherwise, the singular form also includes the plural form. In addition, it should be understood that when the terms "comprise" and / or "include" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.
[0080] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0081] Example 1
[0082] This embodiment provides a sintered copper paste for power device packaging, which includes the following raw materials in percentage by mass: 82% of copper particles coated with a binder and 18% of an organic solvent system.
[0083] in:
[0084] The copper particles are a mixture of spherical and flaky particles, with spherical particles accounting for about 30% and flaky particles accounting for about 70%;
[0085] The particle size of spherical copper particles is 300-500nm, and the particle size of flake copper particles is 1000-1200nm;
[0086] The binder is a mixture of polyvinyl pyrrolidone (PVP) and ethyl cellulose to enhance the surface adhesion of the copper particles;
[0087] The organic solvent system is composed of the following mass percentages: 1% of cerium oxide (CeO2) rare earth antioxidant; 3% of polyvinylidene fluoride (PVDF) forming agent; 1.5% of polyethylene glycol (PEG) leveling agent; 0.8% of carboxymethyl cellulose thickener; 2% of butyl methacrylate crosslinking agent; 1% of polyvinyl alcohol surfactant, 88.7% of solvent diisopropyl alcohol, and 2% of polyurethane resin.
[0088] like Figure 1 As shown, this embodiment also provides a method for preparing a sintered copper paste for power device packaging, comprising the following steps:
[0089] S1. Mix the copper particles with ethylenediaminetetraacetic acid (EDTA, concentration 1%) and citric acid (concentration 0.5%) solution at a solid-liquid mass ratio of 1:15, stir magnetically for 20 minutes to allow the oxide on the surface of the copper particles to react with the complexing agent to form a soluble complex, centrifuge at 6000r / min for 10 minutes, remove the supernatant, add anhydrous ethanol and perform ultrasonic cleaning twice, each time for 5 minutes, centrifuge at 3000r / min for 5 minutes after each cleaning, remove the supernatant to remove the complex and other residues, ensure that there is no oxide layer on the surface of the copper particles, place the cleaned copper particles in a vacuum drying oven at 70°C, and dry for 40 minutes to obtain pure copper particles with no oxide residue on the surface;
[0090] S2, mixing the copper particles after the complex treatment with an ethanol solution of 0.5% polyvinyl pyrrolidone and 0.5% ethyl cellulose, ultrasonicating for 20 minutes, centrifuging at 5000 r / min to remove the supernatant, adding anhydrous ethanol for washing for 5 minutes, centrifuging at 3000 r / min, and removing the supernatant to obtain copper particles coated with a binder;
[0091] S3, dissolving cerium oxide in an alcohol solvent at a concentration of 1%, and magnetically stirring for 30 minutes to form a uniformly dispersed rare earth antioxidant; weighing a molding agent, a rare earth antioxidant, a leveling agent, a thickener, a cross-linking agent, a surfactant and a resin according to a proportion, adding the solvent, and magnetically stirring for 70 minutes to ensure uniform mixing, thereby preparing an organic solvent system;
[0092] S4. Add the binder-coated copper particles into an organic solvent system and stir with a magnetic stirrer for 20 minutes to make the rare earth antioxidant and other organic components in the organic solvent system evenly distributed on the surface of the copper particles, and achieve preliminary antioxidant treatment through chemical adsorption and physical coating; place the mixture in an ultrasonic bath and perform ultrasonic dispersion treatment at a temperature of 25°C for 10 minutes to further enhance the adhesion and dispersion effect of the rare earth antioxidant and the organic components on the surface of the copper particles; place the treated mixture in a centrifuge, control the centrifugal speed at 6000r / min, and the centrifugal time for 10 minutes, remove the supernatant, and degas in a vacuum degasser for 15 minutes to obtain a uniform copper paste.
[0093] like Figure 2 As shown, this embodiment also provides a packaging interconnection structure of a power device, including: a silver-plated active metal welded ceramic substrate, a pure copper heat sink, and a connecting layer for connecting the silver-plated active metal welded ceramic substrate and the pure copper heat sink, wherein the connecting layer is formed by double-sided coated copper paste under pressure-assisted sintering.
[0094] This embodiment also provides a method for preparing a packaging interconnection structure of a power device, comprising the following steps:
[0095] P1. Use a dust-free cloth to clean the surface of the silver-plated active metal welding ceramic substrate and the pure copper heat sink to remove surface dirt and ensure that there is no grease, oxides and other contaminants on the surface to improve the adhesion of the copper paste;
[0096] P2. Coat the copper paste on the connection surfaces of the silver-plated active metal welding ceramic substrate and the pure copper heat sink respectively; the coating thickness is controlled within the range of 150-200 μm to ensure uniform coating and provide a good foundation for subsequent sintering; place the coated silver-plated active metal welding ceramic substrate and the pure copper heat sink in a drying furnace for pre-drying, introduce nitrogen / argon / hydrogen / formic acid atmosphere to avoid oxidation, and control the drying temperature at 100-120°C for 40 minutes to achieve preliminary curing;
[0097] P3. Align and tightly stack the surface of the silver-plated active metal-welded ceramic substrate coated with copper paste and the pure copper heat sink coated with copper paste in a top-to-bottom order, place the stacked assembly on the heating table of the sintering equipment, continuously introduce nitrogen atmosphere to prevent oxidation reaction of the copper paste during heating, heat the equipment to 200-275°C, and apply a pressure of 20MPa for 5 minutes to complete the sintering connection process, so that a dense and high-strength connection layer is formed between the silver-plated active metal-welded ceramic substrate and the pure copper heat sink;
[0098] P4. Gradually lower the temperature of the equipment and slowly cool the sintered stacked assembly to room temperature to ensure that the connection layer does not crack or warp during the cooling process, thereby obtaining the packaging interconnection structure of the power device.
[0099] After testing, the sintered copper paste for power device packaging prepared in this embodiment can well complete the sintering connection between the silver-plated active metal welding ceramic substrate and the pure copper heat sink. The test shows that the thickness uniformity of the connection layer after pre-sintering is good. Figure 3 The method shown tests the thickness at different positions, and the maximum thickness difference is less than 20μm.
[0100] The connection layer after sintering has high strength and stability. Figure 4 As shown in the figure, it can be seen that under the conditions of 200℃ and 20MPa pressure, the shear strength reaches 38.7MPa; under the conditions of 250℃ and 20MPa pressure, the shear strength reaches 59.8MPa. The quality of the connection layer is measured by ultrasonic scanning, and the scanned image is as follows Figure 5 As shown in (a), it can be seen from the figure that the internal structure of the connecting layer is uniform, without obvious defects or voids, which verifies the reliability and practicality of the copper paste of the present invention.
[0101] Example 2
[0102] This embodiment provides a sintered copper paste for power device packaging, which includes the following raw materials in percentage by mass: 83% of copper particles coated with a binder; and 17% of an organic solvent system.
[0103] in:
[0104] The copper particle morphology is a mixture of spherical and flaky particles, with spherical particles accounting for about 40% and flaky particles accounting for about 60%;
[0105] The particle size of the copper particles ranges from 200 to 1200 nm, of which the particle size of spherical particles is 400 to 600 nm and the particle size of flaky particles is 800 to 1200 nm;
[0106] The binder is a mixture of methyl cellulose and epoxy acrylate to further enhance the adhesion and high temperature stability of the particles.
[0107] The organic solvent system is composed of the following mass percentages: 1.5% of lanthanum oxide (La2O3) rare earth antioxidant; 3% of polyacrylate forming agent; 1% of ethoxy modified silicone oil leveling agent; 1% of hydroxypropyl methylcellulose thickener; 1% of butyl acrylate crosslinking agent; 1% of polyoxyethylene octylphenol ether surfactant, 89.5% of solvent triethylene glycol, and 2% of amino resin.
[0108] This embodiment also provides a method for preparing a sintered copper paste for power device packaging, comprising the following steps:
[0109] S1. Mix copper particles with aminotriacetic acid (NTA, concentration 1%) and malic acid (concentration 0.5%) solution at a solid-liquid mass ratio of 1:10, stir magnetically for 15 minutes to react the oxide on the surface of the copper particles with the complexing agent to form a soluble complex, centrifuge at 5000 r / min for 15 minutes, remove the supernatant, add anhydrous ethanol and perform ultrasonic cleaning for 3 times, each time for 5 minutes, centrifuge at 4000 r / min for 5 minutes after each cleaning, remove the supernatant to remove the complex and other residues, ensure that there is no oxide layer on the surface of the copper particles, place the cleaned copper particles in a vacuum drying oven at 60° C., and dry for 50 minutes to obtain pure copper particles with no oxide residue on the surface;
[0110] S2, mixing the copper particles treated with the complex with a 1% methylcellulose solution, ultrasonicating for 25 minutes, centrifuging at 5000 r / min to remove the supernatant, then adding anhydrous ethanol to wash for 10 minutes, centrifuging at 3000 r / min, and removing the supernatant to obtain copper particles uniformly coated with the binder;
[0111] S3, dissolving lanthanum oxide in an alcohol solvent at a concentration of 1%, and magnetically stirring for 40 minutes to form a uniformly dispersed rare earth antioxidant; adding a molding agent, a rare earth antioxidant, a leveling agent, a thickener, a cross-linking agent, a surfactant and an epoxy resin to the solvent in proportion, and using magnetic stirring for 60 minutes to ensure uniform mixing, to prepare an organic solvent system;
[0112] S4. Add the binder-coated copper particles into an organic solvent system and stir with a magnetic stirrer for 30 minutes to make the rare earth antioxidant and other organic components in the organic solvent system evenly distributed on the surface of the copper particles, and achieve preliminary antioxidant treatment through chemical adsorption and physical coating; place the mixture in an ultrasonic bath and perform ultrasonic dispersion treatment at a temperature of 26°C for 15 minutes to further enhance the adhesion and dispersion effect of the rare earth antioxidant and organic components on the surface of the copper particles; place the treated mixture in a centrifuge, control the centrifugal speed at 5000r / min, and the centrifugal time for 15 minutes, remove the supernatant, and degas in a vacuum degasser for 15 minutes to obtain a uniform copper paste.
[0113] This embodiment also provides a packaging interconnection structure of a power device, comprising: a nickel-gold-plated active metal welded ceramic substrate, a nickel-plated copper heat sink, and a connecting layer for connecting the nickel-gold-plated active metal welded ceramic substrate and the nickel-plated copper heat sink, wherein the connecting layer is formed by double-sided coated copper paste under pressure-assisted sintering.
[0114] This embodiment also provides a method for preparing a packaging interconnection structure of a power device, comprising the following steps:
[0115] P1. Use a dust-free cloth to clean the surface of the nickel-gold-plated active metal welding ceramic substrate and the nickel-plated copper heat sink to remove surface dirt and ensure that there is no grease, oxides and other contaminants on the surface to improve the adhesion of the copper paste;
[0116] P2. Coat the copper paste on the connection surfaces of the nickel-gold-plated active metal welding ceramic substrate and the nickel-plated copper heat sink respectively; the coating thickness is controlled within the range of 150-200 μm to ensure uniform coating and provide a good foundation for subsequent sintering; place the coated nickel-gold-plated active metal welding ceramic substrate and the nickel-plated copper heat sink in a drying furnace for pre-drying, introduce nitrogen / argon / hydrogen / formic acid atmosphere to avoid oxidation, control the drying temperature at 100-120°C, and maintain for 50 minutes to achieve preliminary curing;
[0117] P3. Align and stack the surface of the nickel-gold active metal-welded ceramic substrate coated with copper paste and the nickel-plated copper heat sink coated with copper paste from top to bottom, place the stacked assembly on the heating table of the sintering equipment, and continuously introduce a nitrogen-hydrogen mixed atmosphere to prevent the copper paste from oxidizing during the heating process. Heat the equipment to 200-275°C and apply a pressure of 10MPa for 5 minutes to complete the sintering connection process, so that a dense and high-strength connection layer is formed between the silver-plated active metal-welded ceramic substrate and the nickel-plated copper heat sink;
[0118] P4. Gradually lower the temperature of the equipment and slowly cool the sintered stacked assembly to room temperature to ensure that the connection layer does not crack or warp during the cooling process, thereby obtaining the packaging interconnection structure of the power device.
[0119] After testing, the sintered copper paste for power device packaging prepared in this embodiment showed excellent reliability in the connection between the nickel-gold active metal welding ceramic substrate and the nickel-copper heat sink. The thickness uniformity of the connection layer is good. The test shows that the maximum thickness difference is less than 18μm. The stacked structure after sintering has high strength and significant high temperature resistance. The strength of the connection layer after chip mounting is as follows Figure 4 As shown in the figure, it can be seen that under the conditions of 200℃ and 10MPa pressure, the shear strength reaches 32.4MPa; under the conditions of 250℃ and 10MPa pressure, the shear strength reaches 54.1MPa. The ultrasonic scanning results are as follows Figure 5 As shown in (b), it can be seen from the figure that there are no defects inside the connection layer and the density is good, which verifies its application value in high-reliability packaging.
[0120] Example 3
[0121] This embodiment is basically the same as Embodiment 1, except that: this embodiment applies a pressure of 5 MPa, and the remaining raw materials and preparation method steps are basically the same as those in Embodiment 1.
[0122] The strength of the connection layer after chip mounting is as follows Figure 4 As shown in the figure, it can be seen that under the conditions of 200°C and 5MPa pressure, the shear strength reaches 30.2MPa; under the conditions of 250°C and 5MPa pressure, the shear strength reaches 50.3MPa.
[0123] Comparative Example 1
[0124] This comparative example is basically the same as Example 1, except that: in this comparative example, copper paste is only coated on one side of the connection surface of the copper paste silver-plated active metal welded ceramic substrate, and the remaining raw materials and preparation method steps are basically the same as Example 1.
[0125] Through the thermal aging test at 500℃ and 200 hours, it was found that the oxide at the interface of the connecting layer of the single-sided coating design increased significantly. Figure 6 (ac) in the figure shows that the oxides mainly gather at the interface between the substrate and the connecting layer, and the distribution of the oxides is uneven, and the degree of oxidation in the edge area is more serious, resulting in a decrease in the interfacial adhesion of the connecting layer. In the subsequent mechanical strength test, the shear strength of the connecting layer decreased from the initial 30MPa to 15MPa, indicating that the interface oxidation has a significant effect on the strength of the connecting layer.
[0126] In contrast, in Example 1, a design of double-sided copper paste coating is adopted, and copper paste is simultaneously coated on the connecting surfaces of the substrate and the heat sink, thereby effectively preventing the formation and aggregation of oxides at the interface. Figure 6 The (df) in the figure shows that the connection layer prevents the diffusion of oxides into the interior at the interface after the aging test, the internal structure is uniform, and the interface adhesion is good. Under the same test conditions, its shear strength is still maintained above 30MPa, and its reliability is significantly better than that of the single-sided coating design.
[0127] The present invention significantly improves the antioxidant capacity of the connection layer through the innovative design of double-sided copper paste coating, effectively preventing the generation and aggregation of oxides at the interface during high-temperature aging, thereby improving the strength of the connection layer and the reliability of long-term service. In contrast, the single-sided coating design fails to inhibit the formation of interface oxides, resulting in a significant decrease in the strength of the connection layer, which cannot meet the requirements of high-temperature and high-reliability packaging.
[0128] Comparative Example 2
[0129] This comparative example is basically the same as Example 1, except that: no rare earth antioxidant is added to the organic solvent system of this comparative example, and the remaining raw materials and preparation method steps are basically the same as Example 1.
[0130] The shear strength of Example 1 treated with rare earth oxidant and Comparative Example 2 not treated with rare earth oxidant after high temperature aging at 250°C at different times is shown in Figure 7 As can be seen from the figure: the shear strength of the copper paste treated with rare earth oxidants during the aging process is significantly higher than that of the untreated copper paste. The rare earth oxidants effectively inhibit the generation and diffusion of oxides in high temperature environments by forming a stable anti-oxidation barrier layer on the surface of copper particles, significantly improving the mechanical properties and long-term reliability of the connection layer.
[0131] Comparative Example 3
[0132] This comparative example is basically the same as Example 1, except that the copper particles in this comparative example are not subjected to the complex treatment step, and the remaining raw materials and preparation method steps are basically the same as those in Example 1.
[0133] The shear strength test results of the connecting layer of Example 1 treated with the complex and Comparative Example 3 not treated with the complex are shown in Figure 8 ,It can be seen from the figure that the use of complex treatment technology further enables the copper particles to be densified more easily during the sintering process, thereby enhancing the shear strength.
[0134] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A sintered copper paste for power device packaging, characterized in that: The invention comprises the following raw materials in percentage by mass: 75%-85% of copper particles coated with a binder and 15%-25% of an organic solvent system; the organic solvent system comprises a rare earth antioxidant; and further comprises one or more of a molding agent, a leveling agent, a thickener, a cross-linking agent, a surfactant, a solvent and a resin.
2. The sintered copper paste for power device packaging according to claim 1, characterized in that: The binder includes one or more of polyvinyl pyrrolidone, methyl cellulose, ethyl cellulose, epoxy acrylate, acrylate and cellulose acetate.
3. The sintered copper paste for power device packaging according to claim 1, characterized in that: In terms of mass percentage, the organic solvent system comprises: 1%-5% of a molding agent, 0.5%-2% of a leveling agent, 0.5%-1% of a thickener, 1%-3% of a rare earth antioxidant, 1%-3% of a crosslinking agent, 1%-2% of a surfactant, 85%-90% of a solvent and 1%-2% of a resin.
4. The sintered copper paste for power device packaging according to claim 1, characterized in that: The rare earth antioxidant includes one or more of cerium oxide, lanthanum oxide, cerium chloride and lanthanum nitrate.
5. The sintered copper paste for power device packaging according to claim 1, characterized in that: The morphology of the copper particles includes: one or more of spherical, flake or triangular; the particle size of the copper particles ranges from 50 to 2000 nm.
6. The sintered copper paste for power device packaging according to claim 1, characterized in that: The molding agent includes: one or more of polyvinylidene fluoride, polyacrylate, and styrene-butadiene copolymer; the leveling agent includes: one or more of sodium polyacrylate, ethoxy-modified silicone oil, and polyethylene glycol; the thickener includes: one or more of carboxymethyl cellulose, hydroxypropyl methylcellulose, and sodium polyacrylate; the cross-linking agent includes: one or more of butyl methacrylate, butyl acrylate, and polyethylene imine; the surfactant includes: one or more of polyvinyl alcohol, polyoxyethylene octylphenol ether, and sodium dodecylbenzene sulfonate; the solvent is an alcohol organic matter; the resin includes: one or more of polyimide resin, amino resin, and polyurethane resin.
7. The method for preparing the sintered copper paste for power device packaging according to any one of claims 1 to 6, characterized in that: The steps include: S1. Performing complex treatment on the copper particles to ensure that there is no oxide layer on the surface of the copper particles; S2, mixing the copper particles treated with the complex with a binder, removing the supernatant by ultrasonic centrifugation, adding anhydrous ethanol for washing, and removing the supernatant by centrifugation to obtain copper particles coated with a binder; S3, mixing a forming agent, a leveling agent, a thickener, a rare earth antioxidant, a crosslinking agent, a surfactant, a solvent and a resin, and stirring them uniformly to obtain an organic solvent system; S4, mixing the copper particles coated with the binder obtained in step S2 with the organic solvent system obtained in step S3 to obtain the copper paste.
8. The method for preparing the sintered copper paste for power device packaging according to claim 7, characterized in that: Step S1 includes the following steps: S11, dissolving a complexing agent in deionized water to obtain a complexing agent solution; S12, adding copper particles to the complexing agent solution obtained in step S11, so that the oxide on the surface of the copper particles reacts with the complexing agent to form a soluble complex; S13, centrifuging the mixture obtained in step S12 to remove the supernatant, and then washing with anhydrous ethanol and centrifuging to remove the supernatant; S14, drying the cleaned copper particles to obtain copper particles with no oxide on the surface.
9. A packaging interconnection structure of a power device, characterized in that: include: A substrate, a heat sink and a connection layer for connecting the substrate and the heat sink, wherein the connection layer is formed by double-sided coated copper paste according to any one of claims 1 to 6 under pressure-assisted sintering.
10. The method for preparing the packaging interconnection structure of a power device according to claim 9, characterized in that: The steps include: P1. Remove pollutants from the surface of the substrate and heat sink; P2. Coating the copper paste according to any one of claims 1 to 6 on the connecting surfaces of the substrate and the heat sink, respectively, and pre-drying the coated substrate and the heat sink; P3. Align and stack the pre-dried substrate and heat sink, place the stacked assembly in a sintering device, heat the sintering device and apply pressure to complete the sintering connection process, so that a dense and high-strength connection layer is formed between the substrate and the heat sink; P4. Gradually lower the temperature of the sintering equipment and cool the stacked assembly to room temperature to obtain the packaging interconnection structure of the power device.
Citation Information
Patent Citations
SnAgCu leadless brazing filler metal with antioxygenic performance
CN101157162A
Ultraviolet curable resin composition, cured film and laminate
CN109071694A
Environment-friendly anti-oxidation conductive copper paste and preparation method and application thereof
CN114927258A
High-stability sintered copper paste as well as preparation method and application thereof
CN117253651A
Conductive paste
JP2018174125A